Sistem Pendukung Keputusan Dalam Menentukan Kelayakan Bantuan Dana Hibah Fasilitas Rumah Ibadah Menggunakan Metode AHP - Raisyah, Shafira Isra; Zufria, Ilka; Triase, Triase (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
In 2022, the application for grants for houses of worship in North Sumatra has reached 4,857 applicants and houses of worship have received funds of 1,341 recipients. With the number of applications for grants for houses of worship are very high each year, the fact that there is still a shortage of human resources in the implementation of the grant and the funds provided are also not too large. This has caused many houses of worship to be abandoned, applicants for funds are seen competing in obtaining these funds and also cause an unbiased assessment of houses of worship such as the influence of people you already know or so on. It is necessary to use a decision support system, which will make it easier for leaders to make decisions which houses of worship should be immediately given grants and are expected to be on target in choosing them. The research conducted by the author aims to build a website decision support system using the AHP method with the problem of determining the feasibility of Grant Aid House of worship facilities. The results of the decision can give consideration to officials in determining houses of worship that are eligible to receive funds. The result of the research are that there are 5 criteria that will be used, namely proposed funds, cost details, the house of worship, year of establishment of the House of worship, condition of and the level routine of the house of worship. Based on research, the best alternative is Gereja Pantekosta di Indonesia Jemaat Filadelfia Sait Buttu with a total of 0.17 and the lowest score is HKBP Distrik V Sumatera Timur Resort Tiga Dolok Palia Putar with a total of 0.08.